ANALYSIS OF TECHNIQUES USED IN TRANSLATING IDIOMS FROM ENGLISH TO INDONESIAN AS FOUND IN ALL AMERICAN GIRL NOVEL - Arina Khairanis (Vivid: Journal of Language and Literature, 2013)
This article discusses techniques in translating English idioms found in All American Girl novel. The novel is written by an American novelist, Meg Cabot, and translated into Indonesian by Monica Dwi Chresnayani. This research focuses on describing the techniques used by the translator in producing a proper translation. The data are analyzed by comparing idioms from source language with the translation in target language. The writer applies the theory of translation proposed by Vinay dan Darbelnet in analyzing the data. Vinay and Darbellnet in Venuti (2004) proposed several techniques of translation. These techniques are categorized in two models; direct and oblique translation. Direct translation can be applied in; borrowing, calque, and literal translation, while oblique translation can be applied in; transposition, modulation, equivalence, and adaptation. The writer describes the analysis by providing tables along with its narrative description. The result of the research shows that the translator uses two techniques in translating; they are modulation and transposition. For the modulation technique, the writer finds that the translator utilizes some semantic changes and switches some positive forms to negative ones in target language. For the transposition techniques, the translator applies some adjustments of word class and word order. Keywords:  Idiom, Technique, Context